Candida albicans-Induced NETosis Is Independent of Peptidylarginine Deiminase 4 - Guiducci, Eva; Lemberg, Christina; Küng, Noëmi; Schraner, Elisabeth; Theocharides, Alexandre P. A.; LeibundGut-Landmann, Salomé (Frontiers in Immunology, 2018)
Neutrophils are the most abundant innate immune cells and the first line of defense against many pathogenic microbes, including the human fungal pathogen Candida albicans. Among the neutrophils’ arsenal of effector functions, neutrophil extracellular traps (NETs) are thought to be of particular importance for trapping and killing the large fungal filaments by means of their web-like structures that consist of chromatin fibers decorated with proteolytic enzymes and host defense proteins. Peptidylarginine deiminase 4 (PAD4)-mediated citrullination of histones in activated neutrophils correlates with chromatin decondensation and extrusion and is widely accepted to act as an integral process of NET induction (NETosis). However, the requirement of PAD4-mediated histone citrullination for NET release during C. albicans infection remains unclear. In this study, we show that although PAD4-dependent neutrophil histone citrullination is readily induced by C. albicans, PAD4 is dispensable for NETosis in response to the fungus and other common NET-inducing stimuli. Moreover, PAD4 is not required for antifungal immunity during mucosal and systemic C. albicans infection. Our results demonstrate that PAD4 is dispensable for C. albicans-induced NETosis and they highlight the limitations of using histone citrullination as a marker for NETs and PAD4-/- mice as a model of NET-deficiency.